2011
DOI: 10.1158/0008-5472.can-11-0165
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Serum Levels of Cytokines and Other Immune Markers and Risk of Non-Hodgkin Lymphoma

Abstract: While severe immune dysregulation is an established risk factor for non-Hodgkin lymphoma (NHL), it is unclear whether subclinical immune system function influences lymphomagenesis. To address this question, we conducted a nested case-control study within the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial to investigate whether circulating levels of cytokines and other immune markers are associated with future risk of NHL. Selected cytokines [interleukin (IL)-4, IL-6, IL-10, tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 44 publications
10
88
4
Order By: Relevance
“…No direct evidence from our analyses provided support for the previously reported associations between TNF,9 IL138 and IL109, 10, 14 and BCL; TNF‐α,11 IL614 and IL109, 14 and FL; TNF‐α,11 IL5 and IL109 and DLBCL and TGF‐α11 and TNF9 and CLL. However, the direction of most of the previously reported associations is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…No direct evidence from our analyses provided support for the previously reported associations between TNF,9 IL138 and IL109, 10, 14 and BCL; TNF‐α,11 IL614 and IL109, 14 and FL; TNF‐α,11 IL5 and IL109 and DLBCL and TGF‐α11 and TNF9 and CLL. However, the direction of most of the previously reported associations is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 81%
“…As previously reported in a study involving 491 B‐NHL cases and 491 controls,9 we also find a positive correlation between levels of TNF‐α, IL10 and the incidence of all BCL, FL and DLBCL. The associations reported by Purdue et al 10, 11. and Conroy et al 14.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Magnesium deficiency upregulates proinflammatory cytokines and increases oxidative stress, which contribute to the development of NHL. [14][15][16] It activates the redox-sensitive transcription factor nuclear factor kappa-B (NF-kB), whose constitutive activation is being recognized as critical in the pathogenesis of lymphoma and in the progression of EBV-induced malignancy. 17,18 NF-kB mediates various effects of viral infection that contribute to carcinogenesis such as antiapoptosis and stimulation of cellular proliferation.…”
Section: Basic Support For a Role Of Magnesium Status In The Developmmentioning
confidence: 99%
“…A recent case-control study, nested within the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial with a median length of 5 years follow-up from blood collection to case diagnosis, conducted by Purdue et al (2011) showed that elevated sTNF-R1 and sCD27 levels were associated with higher risk of developing NHL. These associations remained significant in analyses of cases diagnosed longer than 6 years following blood collection.…”
Section: Lymphoma Blood Biomarkers Among the General Populationmentioning
confidence: 99%